St. Lucia : Statistical Appendix. (IMF Staff Country Reports; Country Report, 2006)
The report highlights the IMF projections and estimates of St. Lucia's basic data indicators, its GDP by economic activity at constant and current factor cost, selected data on the banana industry, operations of the central government, operations of the consolidated public sector, monetary survey, summary operations of the Eastern Caribbean Central Bank, consolidated accounts of the commercial banks, structure of public debt 1999/2000-2004/05, selected tourism statistics, direction of trade, imports and prices of petroleum products, merchandise trade volumes, unit values, terms of trade, imports by SITC category, et cetera.